Ministernotomy approach to aortic arch inclusion and frozen elephant trunk in the treatment of acute Stanford A aortic dissection - Wang, Weitie; Wang, Yong; Piao, Hulin; Zhu, Zhicheng; Li, Dan; Wang, Tiance; Liu, Kexiang (Frontiers in Cardiovascular Medicine, 2022)
This study aimed to report our results of ministernotomy approach to Liu’s aortic root repair technique, Liu’s aortic arch inclusion technique with frozen elephant trunk (FET) in the treatment in type A aortic dissection (TAAD). We retrospectively analyzed data on 68 Stanford A aortic dissection patients from October 2017 to March 2020. All patients underwent Liu’s aortic root repair technique, Liu’s aortic arch inclusion technique with FET and mild-moderate hypothermic circulatory arrest combined with ministernotomy approach. 154 TAAD patients between January 2014 and December 2016 underwent complete sternotomy were selected as control group. Clinical characteristics, data during operation, in-hospital and postoperative outcomes of these patients were observed. The mean hypothermic circulatory arrest time in ministernotomy Patients was 39.3±7.9 min, aortic cross-clamp time was 105.9±12.8 min, cardiopulmonary bypass time was 152.8±24.3 min. Three patients died of multiple organ dysfunction syndrome in ministernotomy Patients. Perioperative temporary neurological dysfunction occurred in three (4.41%) patients, and 53 (77.9%) patients did not require any blood product transfusion during and after operation in ministernotomy Patients. Postoperative CT angiography (CTA) examination at 6-32 months showed excellent outcomes except in three (4.41%) cases where arch false lumen patency persisted. The Liu’s aortic root repair technique, Liu’s aortic arch inclusion technique with FET and mild-moderate hypothermia circulatory arrest simplify the surigical procedure and reduce bleeding, which can be accomplished through minimally invasive approach.